2002
DOI: 10.1080/0007166021000025037
|View full text |Cite
|
Sign up to set email alerts
|

Passage rate through the anterior digestive tract of broiler chickens fed on diets with ground and whole wheat

Abstract: 1. Birds were fed diets containing ground or whole wheat and titanium dioxide for 10 min, followed by dissection of 4 birds per treatment after 30, 60, 90, 120, 150 and 180 min. 2. The crop, proventriculus and gizzard, duodenum, jejunum, and ileum from each bird were dried and combusted, and titanium content in each section was determined. 3. Significant amounts of titanium were found in the small intestine of the birds as soon as 30 min after being given feed containing titanium, and significant amounts had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 15 publications
7
41
1
Order By: Relevance
“…The increased gizzard weight was also observed in chickens fed whole grain (Svihus and Hetland, 2001;Plavnik et al, 2002;Svihus et al, 2002;Santos et al, 2006). This increased gizzard weight is due to the increase in grinding necessary to process the particle size of whole grains (Roche, 1981;Gabriel et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…The increased gizzard weight was also observed in chickens fed whole grain (Svihus and Hetland, 2001;Plavnik et al, 2002;Svihus et al, 2002;Santos et al, 2006). This increased gizzard weight is due to the increase in grinding necessary to process the particle size of whole grains (Roche, 1981;Gabriel et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…In fact, in the current research, gizzard digesta content was higher in birds fed corn than in birds fed wheat at all ages (although the differences were significant only at 17 wk of age), data that are consistent with the harder endosperm of the corn. In addition, the proportion of coarse particles (> 2,500 μm) was higher for the corn than for the wheat diets, which may also increase the content and weight of the gizzard Svihus and Hetland, 2002). Gizzard pH, however, was not affected by the main cereal of the diet at any age, in agreement with data of Nir et al (1994a) in 3-week-old broilers fed mash diets.…”
Section: Gastrointestinal Tract Traitssupporting
confidence: 79%
“…In broilers, the passage velocity through the anterior digestive tract is slower than in pheasants. After giving a feed containing titanium oxide as a marker, Svihus et al (2002) found that passage through the small intestine of the birds took 30 min and that a significant amount had passed the small intestine after 120-150 min. In an experiment where pheasants were given barium sulfate as a contrast agent directly into the crop, the time passage was for stomach 10-45 min, for small intestines 45-120 min, for large intestines 120-150 min, and for cloaca 150-240 min, respectively (Ritchie et al 1994).…”
Section: Discussionmentioning
confidence: 99%